The August 2010 Phreatic Eruption of Mount Sinabung, North Sumatra - Sutawidjaja, Igan S.; Prambada, O.; Siregar, D. A. (Indonesian Journal on Geoscience, 2013)
DOI:Â 10.17014/ijog.v8i1.155Mount Sinabung, located in Karo Regency, North Sumatra Province, is a strato volcano having four active craters. Since its latest eruption about 1,200 year ago, a phreatic eruption occurred on August 27th, 2010. The eruption took place in Crater-I, which was initiated by a greyish white plume and then followed by black plumes as high as 2000 m above the crater. Altered rock fragments and ash were erupted during this event. The altered rocks show a development of argillic alterations which was formed in the hydrothermal system in depth. The alteration zone is formed along the northeast-southwest and northwest-southeast trend across the three craters. All of the craters are actively discharging solfataric gases, of which sulphur deposits are resulted, and they have been quarried by the local people. The age of the latest magmatic eruption was dated by 14C method from the charcoal sample found in the pyroclastic flow deposits near Bekerah Village.